Gambaran Hasil Pemeriksaan Kadar High Density Lipoprotein (HDL) dan Low Density Lipoprotein (LDL) pada Penderita Obesitas di Rumah Sakit Umum Daerah Syekh Yusuf Kabupaten Gowa - Nirmala Ridayani; Nurwahidah Fa'al Santri; Rizman Naim (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2018)
HDL cholesterol is a lipoprotein that contains a lot of protein and a little fat. HDL plays a role in reversing cholesterol transport, which allows the liver to remove excess cholesterol in peripheral tissues. Cholesterol-LDL is the lipoprotein that carries the most cholesterol. The purpose of this study was to describe the levels of High Density Lipoprotein (HDL) and Low Density Lipoprotein (LDL) in obese patients at the Syekh Yusuf Regional General Hospital in Gowa Regency. This study used serum samples obtained from the blood of obese patients in Syekh Yusuf Hospital, Gowa Regency, each of 5 people taken using the purposive sampling method. Data obtained from the results of the examination of HDL and LDL cholesterol in obese patients in Syekh Yusuf Hospital, Gowa Regency, the lowest HDL was 38 mg / dl and the highest was 48 mg / dl and the lowest LDL examination was 130 mg / dl and the highest 181 mg / dl. It can be concluded that obese patients in Syekh Yusuf Hospital, Gowa Regency, have 80% abnormal HDL and LDL cholesterol levels.